Effect of the planting position of slips in the pineapple cv 'Pérola' cultivation - Gadélha, Ricardo Sérgio S.; Vasconcellos, Hélio de O. (Pesquisa Agropecuaria Brasileira, 2014)
The effect of two pineapple (Ananas comosus (L) Merr.) Cv. 'Pérola' planting systems were studied as following: slips in the vertical planting position and slips in the inclined planting position. There were statistical difference at the level of 1% to weight, diameter and length of the fruit, number of the slips and plant height from the vertical system. No statistical difference was found to crown, crown weight, total fruit acidity, total soluble solids and number of leaves.